HOW TO IMPROVE LIBRARIANS PROFESSIONALITY IN ERA O F SOCIETY 5.0? - Wijonarko Wijonarko (Department Library of Governance Institut of Home Affairs, 2020)
Problem Statement: One of the problems in this research is the lack of interest of readers in reading printed books and prefers to use internet media in search of information. Besides that, technology-based facilities are still not fully provided in libraries and limited human resources in libraries as a challenge for librarians. Librarian attitude and ability is needed to attract readers' interest in utilizing media provided by the library. Purpose: The purpose of this study is to investigate efforts to improve the professionalism of university librarians in dealing with users in Era Society 5.0 in order to improve the quality of library services as a means of developing knowledge and increase the interest of users in the use of library facilities. Methods: The research method used is descriptive method which describes the phenomena that occur and explains the criteria of professional librarians in the era of society. Result: The interest of users in the Jatinangor IPDN library environment in using the internet to search for information is higher than reading books in the library. Yet according to the results of the questionnaire also showed that 100% of respondents as a library stated the importance of the existence of the library. Conclusion: In an effort to increase the professionalism of librarians in the era of society 5.0, it is necessary to develop the soft skills of librarians. Soft skills that must be possessed by librarians include listening skills, communications skills, and public relations skills. Librarians should deepen and understand the marketing profession in an effort to attract the interest of users.